Setting Time Pada Bone Cement - Octarina; Rahmania, Fadila; Nauli Komala, Olivia (Jurnal Kedokteran Gigi Terpadu, 2025)
Bone cement is a filling material for bone defects consisting of a mixture of powdered biomaterials and a liquid so that it will harden in the body. The bone cement must be biocompatible, osteoconductive, osteoinductive, having good mechanical properties, and filling bone defects. Several studies have stated that good bone cement is bone cement with an optimal setting time. The setting time of bone cement is related to minimally invasive treatment. This article reviews the optimal setting time of several biomaterials that are often used in both medicine and dentistry.